2017
DOI: 10.1002/ejic.201700604
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Reagents Featuring a 1,1′‐Bis(o‐carborane) Ligand Platform

Abstract: Abstract:The synthesis of two bis(carboranyl) (bc) magnesium reagents is described. Treatment of 1,1′-bis(o-carborane) (H 2 -bc) or 8,8′,9,9′,10,10′,12,12′-octamethyl-1,1′-bis(o-carborane) (H 2 -Mebc) with Mg(nBu) 2 in 1,2-dimethoxyethane (DME) affords (bc)Mg(DME) 2 (1a,b) as crystalline solids. The magnesium compounds, which have been characterized by NMR spectroscopy and single-crystal X-ray crystallography in the case of 1a, serve as competent Grignard-type reagents to generate bc-con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
0
19
0
2
Order By: Relevance
“…Er berichtete im European Journal of Inorganic Chemistry über Bis(carboranyl)magnesium-Reagentien. [4] TREE Awardees [7] Humboldt-und Bessel-Forschungspreise 2017/2018…”
unclassified
“…Er berichtete im European Journal of Inorganic Chemistry über Bis(carboranyl)magnesium-Reagentien. [4] TREE Awardees [7] Humboldt-und Bessel-Forschungspreise 2017/2018…”
unclassified
“…53,54 Analogously to carboranes, metalation of biscarboranes is the main route for their carbon vertex functionalization. [55][56][57] We found that the addition of two equivalents of KHMDS to the solution of biscarborane leads to its complete deprotonation as evidenced by the appearance of two new signals in the 13 C NMR spectrum in THF at 83.2 ppm, corresponding to the intercluster C−C bond, and 115.5 ppm, corresponding to the metalated carbon atoms (cf. 65.2 ppm for C(H) and 73.5 ppm for C(C) carbon atoms for the parent neutral biscarborane) (Scheme 3).…”
Section: Resultsmentioning
confidence: 97%
“…Spokoyny und seine Gruppe entwickeln atompräzise Clustersynthesen. Er berichtete im European Journal of Inorganic Chemistry über Bis(carboranyl)magnesium‐Reagentien …”
Section: Ausgezeichnet …unclassified